2018
DOI: 10.24176/simet.v9i1.1665
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Suhu Pengadukan Terhadap Yield Biodiesel Dari Minyak Jelantah

Abstract: ABSTRAKBiodiesel merupakan sumber energi alternatif pengganti minyak diesel, yang dapat dibuat dari senyawa tri gliserida dengan melalui proses reaksi transesterifikasi dengan menggunakan ethanol dan katalis KOH. Salah satu senyawa tri gliserida yang dapat digunakan sebagai bahan baku pembuatan biodiesel adalah minyak jelantah yang merupakan limbah minyak kelapa sawit. Parameter yang dapat digunakan sebagai tolok ukur dalam penelitian adalah jumlah yield biodiesel yang dihasilkan, dengan variasi suhu pengaduka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Viscosity is a number that states the amount of resistance of a liquid material to flow or the size of the amount of shear resistance of a liquid material. Wahyuni found that the higher of the viscosity, the thicker and more difficult liquid material to flow [21]. From Figure 4 it can be seen that at 90 minutes reaction time an increase in viscosity occurs, due to incomplete biodiesel manufacturing process because the boiling point of methanol is 64.7 0 C, then methanol will quickly evaporate before the perfect biodiesel process occurs.…”
Section: The Effect Of Reaction Time To the Viscositymentioning
confidence: 97%
“…Viscosity is a number that states the amount of resistance of a liquid material to flow or the size of the amount of shear resistance of a liquid material. Wahyuni found that the higher of the viscosity, the thicker and more difficult liquid material to flow [21]. From Figure 4 it can be seen that at 90 minutes reaction time an increase in viscosity occurs, due to incomplete biodiesel manufacturing process because the boiling point of methanol is 64.7 0 C, then methanol will quickly evaporate before the perfect biodiesel process occurs.…”
Section: The Effect Of Reaction Time To the Viscositymentioning
confidence: 97%
“…As a result, there is a demand for oil fuel replacements such as biodiesel [3] [4]. Biodiesel is frequently used as a petroleum substitute since it does not necessitate adjustments to machinery or new equipment [5]. This does not always apply to bioethanol, typically mixed with gasoline [6].…”
Section: Introductionmentioning
confidence: 99%